Eksplorasi Etnobotani Sebagai Obat Tradisional Masyarakat Desa Duko Kecamatan Rubaru - Sumenep - Argus, Argus; Zahiroh, Syarifahtuz; Ali, Mahrus (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic), 2024)
The utilization of plants as traditional medicine has been known for a long time by the people of Duko Village, Rubaru Subdistrict, Sumenep District. However, there is no data that can be used as an archive about plants in Duko Village, Rubaru District, Sumenep Regency. This study aims to determine the exploration of ethnobotanical diversity as traditional medicine and its parts used in traditional medicine and how it is utilized. This research is a non-experimental qualitative descriptive research and literature study. This research used field survey methods, semi-structured interviews, and documentation. This research was conducted in March-May 2023 in Duko Village, Rubaru District, Sumenep Regency. Sampling was carried out using purposive sampling technique in three hamlets, namely East Pedatar Hamlet, West Pedatar Hamlet, and Laok Lorong Hamlet, so that 97 respondents were obtained. Data analysis in this study used the Use Value Species (Uvs) method. The results showed that there were 107 species used by the people of Duko Village as traditional medicine to treat various diseases. Plant parts used include leaves with a percentage of 51%, fruit 26%, rhizomes 14%, flowers 11%, seeds 8%, tubers 7%, roots 7%, sap 6%, stems 4%, bark 2%, and plant hair parts 1%. Ways of utilizing plants in medicine include boiling, extracting, mashing, consuming directly, and roasting